2020
DOI: 10.1371/journal.pone.0244282
|View full text |Cite
|
Sign up to set email alerts
|

Early myocardial damage and microvascular dysfunction in asymptomatic patients with systemic sclerosis: A cardiovascular magnetic resonance study with cold pressor test

Abstract: Purpose Cardiac involvement in Systemic Sclerosis (SSc) is increasingly recognized as a mayor cause of morbidity and mortality. The aim of present study is to investigate the early stages of cardiac involvement in SSc by Cardiovascular magnetic resonance (CMR), combining the non-invasive detection of myocardial inflammation and fibrosis using T2 and T1 mapping techniques and the assessment of microcirculatory impairment through perfusion response to cold pressor test (CPT). Methods 40 SSc patients (30 female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Therefore, the assessment of institution-specific reference ranges with established scanner- and sequence-specific T 2 values in healthy volunteers are strongly recommended ( 2 ). With scanner- and sequence-specific reference values as a prerequisite, it was demonstrated that T 2 values in studies of specific inflammatory conditions such as myocarditis ( 3 ), systemic sclerosis ( 37 ), and sarcoidosis ( 35 ) can unequivocally be used to identify myocardial injury. Therefore, the significant difference in T 2 relaxation time that was found in patients using the 3D but not the 2D T 2 mapping merits special attention, as this might suggest better sensitivity to detect tissue alterations with the proposed high-resolution motion-registered radial 3D T 2 mapping technique at 1.5T.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the assessment of institution-specific reference ranges with established scanner- and sequence-specific T 2 values in healthy volunteers are strongly recommended ( 2 ). With scanner- and sequence-specific reference values as a prerequisite, it was demonstrated that T 2 values in studies of specific inflammatory conditions such as myocarditis ( 3 ), systemic sclerosis ( 37 ), and sarcoidosis ( 35 ) can unequivocally be used to identify myocardial injury. Therefore, the significant difference in T 2 relaxation time that was found in patients using the 3D but not the 2D T 2 mapping merits special attention, as this might suggest better sensitivity to detect tissue alterations with the proposed high-resolution motion-registered radial 3D T 2 mapping technique at 1.5T.…”
Section: Discussionmentioning
confidence: 99%
“…For T1 mapping, prior COVID-19 studies have used an array of pulse sequences that vary with respect to saturation/inversion pulse design, sampling interval, and fitting algorithm. 48-50,5-80,51,52,61,72,82-84,86,87 Similarly, among the T2 mapping studies reported, different pulse sequences, fitting algorithms, and signal equations have been used to estimate decay curves 48,49,51,52,61,72,76-80,82-87 —each of which is capable of impacting the derived T2. Additionally, as is the case for LGE, variable spatial resolution provides a potential source of data heterogeneity of particular importance to the post-COVID athlete, given that endurance and strength-trained athletes can manifest differential LV remodeling 90,91 and that some studies have reported athletes to manifest increased LV trabeculations 92 (providing a source of partial voxel admixture of LV blood pool and myocardium).…”
Section: Technical Considerations Regarding Heterogeneity In Lge and ...mentioning
confidence: 99%
“…Another study found that, in addition to higher ECV, SSc patients also had less myocardial blood flow augmentation (measured by CMR perfusion imaging) when experiencing a cold pressor test (hand immersion in cold water) compared to healthy controls. This muted vasodilatory response was favored to represent microvascular dysfunction in this population ( 63 ). Higher baseline ECV also correlates to risk of cardiovascular events among SSc patients with normal echocardiograms who are monitored over time.…”
Section: Left Ventricular Dysfunctionmentioning
confidence: 99%